Guerra, comunidad y distancia. Notas tentativas sobre política indígena a partir de las articulaciones bélicas - Cordero, Guido (EDITORIAL DE LA UNIVERSIDAD NACIONAL DEL SUR, 2021)
This article develops an argument regarding the conceptualization of political units in the indigenous society in the 19th century. For this reason, previous works related to the characterization of the indigenous raids are reviewed. In particular, the fundamental features of a protocol are described, consisting of a set of necessary and regulated actions, which accompanied the execution of major war incursions, but which were not present in others of lesser importance. This asymmetry will be put in relation to a theoretical reflection on Mapuche notions of distance and social closeness, from which a possible meaning for the aforementioned label will be proposed. Based on this, it will be argued that the most productive political delimitation for the analysis of indigenous politics of that period is the social and ritual community of the lof.